Biochemical analysis of liver and muscles of Synodontis schall fish species as a tool for pollution assessment on the White Nile River at south of Khartoum City, Sudan - Gaafar K. Nogod; Leila M. A. Hamed; Hythem S.A. Saeed; Abdellah, Abdelmonem M. (IJRDO-Journal of Applied Science, 2021)
Synodontis schall is important fish species that consumed popularly in Khartoum City restaurants. This study aimed to determinate the levels of heavy metals and enzyme activities in the liver and muscles of this fish species. Ethanol extract was taken for the determination of cholesterol, total lipid contents in fish muscles. While saline extract was used for the estimation of glucose, total protein, albumin, globulin and enzyme e.g., GOT, GPT, LDH, CPK and amylase. The concentrations of heavy metals were carried out by the flame atomic absorption spectrophotometer (UNICAM 929). Result indicated that there were no significant differences between enzyme activities in the liver extract of the tested samples and control. The lead (Pb) level in the liver was found to be higher than that in the muscle, whereas the copper (Cu) level in the muscle was found to be higher than that in the liver. It may be concluded that the maximum cadmium (Cd) concentration in the liver were remarkably higher than the maximum level set by the Commission Regulation while its concentration in the muscle tissues were slightly violated the recommended maximum level. Regular monitoring of biological analysis for fish species in the study area is of paramount importance.